The six wives of Henry VIII [videorecording (DVD)] - Michell, Keith; Crosbie, Annette, 1934-; Tutin, Dorothy, 1930-2001; Stallybrass, Anne; Hale, Elvi; Pleasence, Angela; Crutchley, Rosalie, 1921-1997; McElhone, Natascha, 1969-; May, Jodhi, 1975-; Gregory, Philippa (BBC Video ; Distributed by Warner Home Video, 2006)
The six wives of Henry VIII: A six-part chronicle of England's early 16th century, recounting the turbulent life and times of King Henry VIII through the eyes and travails of his wives.